Dukungan Pemerintah Dan Strategi Keberlanjutan Bisnis Ukm Korea Selatan Di Tengah Pandemi Covid 19 - Hidayati, Ratnaningsih; Rachman, Nadya Megawati (IMAGE : Jurnal Riset Manajemen, 2020)
Global pandemic of COVID-19 has bee creating economic disruption in many countries including South Korea. The decline in the trade sector due to the COVID-19 pandemic does not only affect large-scale industries. The Small and Medium Enterprises sector is also affected by the impact of the implementation of various policies in place to anticipate the spread of this virus. This study aims to provide an overview of government policies and business strategies for South Korean SMEs in the midst of the COVID-19 Pandemic and this study is also expected to provide input for the Government to design appropriate, fast and quality economic recovery programs for SMEs affected by COVID-19. . This paper uses a qualitative approach. The data collection technique was carried out through literature study / literature study and interviews with the Republic of Indonesia Trade Representative in South Korea. The results showed that as a country that was first affected by COVID-19, the response of the South Korean government was relatively fast and sufficient to guarantee business continuity for SMEs, there are five main policies implemented by the South Korean Government and five Business Strategies of SMEs in dealing with COVID- 19.